DEFLECTED MODE OF STEEL PRISMATIC SLUGS AT HEATING. Message 2. Influence of creep on deflected mode of slugs - V. I. Timoshpolskij; V. E. Rotenberg; I. V. Fain; M. L. German; S. M. Kabishov (Литьë и металлургия)
The method of calculation of plastoelastic deformations and stresses of prismatic slugs of rectangular section at their heating in metallurgical furnaces is worked out.